Axisymmetric Lamb's problem in a semi-infinite micropolar viscoelastic medium. (1996) - Biswas, P. K.; Sengupta, P. R.; Debnath, Lokenath
Abstract : A study is made of the axisymmetric problem of wave propagation under the influence of gravity in a micropolar viscoelastic semi-infinite medium when a time varying axisymmetric loading is applied on the surface of the medium. Special attention is given to the effects of gravity which induces a kind of initial stress of a hydrostatic nature on the wave propagation.